Microbial transglutaminase induced controlled crosslinking of gelatin methacryloyl to tailor rheological properties for 3D printing - Zhou, Miaomiao (2020)
Gelatin methacryloyl (GelMA) is a versatile biomaterial that has been shown to possess many advantages such as good biocompatibility, support for cell growth, tunable mechanical properties, photocurable capability, and low material cost. Due to these superior properties, much research has been carried out to develop GelMA as a bioink for bioprinting. However, there are still many challenges, and one major challenge is the control of its rheological properties to yield good printability. Herein, this study presents a strategy to control the rheology of GelMA through partial enzymatic crosslinking. Unlike other enzymatic crosslinking strategies where the rheological properties could not be controlled once reaction takes place, we could, to a large extent, keep the rheological properties stable by introducing a deactivation step after obtaining the optimized rheological properties. Ca2+-independent microbial transglutaminase (MTGase) was introduced to partially catalyze covalent bond formation between chains of GelMA. The enzyme was then deactivated to prevent further uncontrolled crosslinking that would render the hydrogel not printable. After printing, a secondary post-printing crosslinking step (photo crosslinking) was then introduced to ensure long-term stability of the printed structure for subsequent cell studies. Biocompatibility studies carried out using cells encapsulated in the printed structure showed excellent cell viability for at least 7 d. This strategy for better control of rheological properties of GelMA could more significantly enhance the usability of this material as bioink for bioprinting of cell-laden structures for soft tissue engineering.